PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 4 SUNGAI SIPUT KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Widarti, Widarti; Noviana, Eddy; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Background problem in this research is the low yields learn science student, can be seen in the value of the students of the 20 students who completed only 7 students 13% and students who did not complete 13 people (65%) with the average value of the class is 56,25. KKM predetermined school is 65. This research is the Classroom Action Research (CAR) conducted to improve learning outcomes IPA fourth grade students of SD Negeri 4 Sungai Siput to implement cooperative learning model type Two Stay Two Stray. At the first meeting of the first cycle of teacher activity percentage 58.33% with enough categories, the second pertemuam increased to 66.66% in both categories. In the second cycle the first meeting with a percentage of 75.00% with a good category and at the second meeting increased to 83.33% with very good category. Activities of students has increased, in the first cycle of the first meeting of 58.33% with enough categories and the second meeting increased to 70.83% in both categories. While in the first meeting of the second cycle of student activity increased to 79.17% in both categories, and the second meeting increased to 83.33% with very good category. The average results of study before the application is increased 56.25 to 66.00 in the first cycle and increased again to 77.75 in the second cycle. While classical completeness in the first cycle and the second cycle is reached. The implementation of cooperative learning model Two Stay Two Stray can improve learning outcomes IPA fourth grade students of SD Negeri 4 Sungai Siput.Keywords : Cooperative Model Type TSTS, Science Learning Outcomes